Utilizing Dhatu Handmade YouTube Content as a Learning Medium for Procedural Text Writing Based on Local Wisdom - Saputri Ainaul Mardiyah; Elen Inderasari; Nurus Saadah (Tabasa: Jurnal Bahasa, Sastra Indonesia, dan Pengajarannya, 2025)
The development of the digital era has significantly changed the style of education, making the learning process more interactive. In Indonesian language learning, there are four skills, namely listening, speaking, reading, and writing. Writing is a bridge for someone to convey their ideas and aspirations. This study aims to determine the quality of writing by students at Taqiyya Rosyida Junior High School after using the Dhatu Handmade YouTube account as a learning medium. This account was chosen because it suits the needs of students and focuses on handicrafts, so that students will indirectly learn about cultural arts. Learning using YouTube can help students understand and apply procedural texts in writing, so that students become more independent in their learning. The research method used was descriptive qualitative with a case study type of research. The case study approach is a process in which the researcher observes learning comprehensively, starting from the interaction between teachers and students, the use of YouTube media during learning activities, to changes in students' writing results. Data collection techniques included observation, interviews, and documentation. Data analysis was carried out through the steps of grouping data, presenting data findings, and drawing conclusions to obtain the learning process and results. The subjects of this study included Indonesian language teacher, Indaryati, S.Pd., and male seventh-grade students at Taqiyya Rosyida Junior High School. The results showed that all groups 1-5 obtained scores above the minimum passing grade, ranging from 80 to 90, indicating that the use of YouTube media had a positive contribution to students' writing skills. The assessment, which was conducted using the covered structure (title, purpose, tools, materials, steps) and linguistic aspects (imperative sentences, temporal conjunctions, and detail words). Perkembangan era digital telah mengubah gaya Pendidikan secara signifikan sehingga proses pembelajaran berlangsung lebih interaktif. Dalam pembelajaran Bahasa Indonesia, terdapat empat keterampilan yaitu menyimak, berbicara, membaca, dan menulis. Menulis menjadi jembatan seseorang dalam menyalurkan gagasan dan aspirasi. Penelitian ini bertujuan mengetahui kualitas tulisan siswa SMP Taqiyya Rosyida setelah memanfaatkan akun Youtube Dhatu Handmade sebagai media belajar. Akun ini dipilih karena menyesuaikan kebutuhan siswa, berfokus pada seni kerajinan tangan, sehingga secara tidak langsung siswa akan belajar seni budaya. Pembelajaran dengan menggunakan Youtube, dapat membantu siswa dalam memahami dan mengaplikasikan teks prosedur menjadi tulisan, sehingga siswa lebih mandiri dalam belajar. Metode penelitian yang digunakan yaitu deskriptif kualitatif dengan jenis penelitian studi kasus. Pendekatan studi kasus merupakan proses peneliti mengamati pembelajaran secara komprehensif, mulai dari interaksi guru dan siswa, pemanfaatan media Youtube selama kegiatan belajar, hingga perubahan hasil tulisan siswa. Teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi. Analisis data dilakukan melalui langkah-langkah mengelompokkan data, menyajikan temuan data, dan menarik kesimpulan untuk memperoleh proses dan hasil pembelajaran. Subjek penelitian ini meliputi guru Bahasa Indonesia, Indaryati, S.Pd., serta siswa kelas VII putra SMP Taqiyya Rosyida. Hasil penelitian menunjukkan bahwa seluruh kelompok 1-5 memperoleh nilai di atas KKTP, yaitu berkisar antara 80-90, sehingga dapat dinyatakan bahwa penggunaan media Youtube memberikan kontribusi positif terhadap keterampilan menulis siswa. Penilaian yang dilakukan meliputi struktur (judul, tujuan, alat, bahan, langkah-langkah) dan aspek kebahasaan (kalimat perintah, konjungsi temporal, kata perincian).